Effect of long-term fertilisation of Calcisols on organic carbon sequestration in marine climate in Estonia - V. Loide (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2023)
The aim of this work was to investigate the effect of long-term (45-year) fertilization of the crop rotation on soil organic carbon concentration (SOC%) changes in different periods of the experiment and its trend under conditions of more northerly marine climate changes. In this work, the data of the long-term NPK fertilization experiment of sandy loam Calcisols located in Northern Estonia (longitude 58.584816, latitude 24.422128) have been used. The crop rotation was divided into six blocks: potato-spring barley-spring barley under sowing with forage grasses – 1y and 2y forage grasses-winter rye. Different combinations of mineral (N 40—180; P 18—54; K 50—105 kg ha−1) and organic (manure (FYM) 30 and 60 Mg ha−1) fertilizers were used in the study. Two periods were observed: the last 20y vegetation period was 10% warmer and 15% less rainy than the earlier period. Under conditions of climate warming, the yield of barley and potatoes increased the most, especially with manure application. SOC% increased from 2.01 to 2.04 under the influence of mineral fertilizers, and from 2.08 to 2.22 with mineral + FYM. The soil is sustainable if manure is used at least 5–10 Mg ha−1 per y−1.